No Little Plans: Alternative Building and Transportation Visions for Toronto. CITY OF TORONTO ARCHIVES - Rogers, Simon Patrick (Archivaria, 2016)
No Little Plans: Alternative Building and Transportation Visions for Toronto. CITY OF TORONTO ARCHIVES. 17 September 2015–30 August 2016. Curated by MARK OSBALDESTON